Community Service Based on A Training Method for Making Liquid Hand Sanitizers to Prevent The Spread of COVID-19 in Tegalsari Kulon Progo - Astuti, Erna; Sugihartini, Nining; Zainab, Zainab; Novitasari, Putri Rachma (Universitas Ahmad Dahlan, 2023)
Background: During this Covid-19 pandemic, the use of hand sanitizer needs to be encouraged to maintain hand hygiene. During endemic and new normal times, the use of hand sanitizer is highly recommended. The hand sanitizers circulating in the market are still predominantly made from alcohol. Hand sanitizer in liquid or spray form is more effective than gel hand sanitizer. Contribution: The purpose of this community service is to improve knowledge in making liquid hand sanitizers for the people of Tegalsari Hamlet. With this training, the community can provide hand sanitizer independently. Method: The steps of training were to share videos of making hand sanitizers, organize discussion sessions via Google Meeting, send materials for making hand sanitizers to participants, and did training. The method of making hand sanitizer follows WHO standards. The training participants were 28 teenagers from Tegalsari. Results: From the evaluation, it is known that there is an increase in the ability to make hand sanitizer by 50.74% and an increase in community skills. Conclusion: The training participants succeeded in making hand sanitizer. This activity got a very good response from training participants. Participants are very enthusiastic and stated that this activity is very useful for them. It was proven that the participants were capable to produce hand sanitizers independently